Pathogenesis and molecular mechanisms of mutant TIE2-driven venous malformation - Lindsay J. Bischoff; Elisa Boscolo (Angiogenesis, 2026)
Venous malformation (VM) is the most common subtype of vascular malformation. Due to the chronic nature of this disorder, VM patients face significant morbidity and complications throughout their lives. Current therapeutic options can be limited, but recent advances in understanding the cellular and molecular mechanisms that underly VM pathogenesis provide hope for the discovery of more effective targeted therapies. These advances arise from a greater understanding of the cellular effects of VM-causative mutations, which has been aided by the development of more advanced and physiologically relevant model systems. In this review, we begin by providing a brief overview of the clinical characteristics and genetic driver mutations of the most common subtypes of all vascular anomalies (including vascular tumors and vascular malformations), providing context for our more detailed discussion of these aspects of VM. We further summarize the current treatment options available for VM patients and the advancements that have been made in the use of targeted therapies for these patients. We further discuss recent advances in the development of model systems that can be used to study VM pathogenesis. Finally, we focus this review on the mechanisms that are downstream of mutant TIE2, discussing structural features of the receptor, TIE2 signaling pathways, and its roles in vascular physiology and VM pathology.